Annual Plan 2001-02 - Planning Commission (Planning Commission, 2001)
The year 2001-02 being the terminal year of the Ninth Five Year Plan, the Annual Plan for the year attempts a comprehensive review of the objectives and strategies of the Ninth Plan taking stock of the performance of the country’s economic development in the first four years vis-a-vis the targets. The Annual Plan also highlights the areas of emphasis needed for consolidating the physical and financial performance of the Ninth Plan in the terminal year. An attempt has been made to address the areas of success and failure, both in physical and financial terms, in relation to the targets for the respective annual plans and the Ninth Five Year Plan as a whole.
Planning Commission Government of India
Planning Commission Government of India